Frontier analysis and agricultural typologies - Eduardo Maruyama Sasaki; Phoebe Scollard; Maribel Elías; Francis Mulangu; Abdoulaye Seck (University of Bonn, Center for Development Research (ZEF), 2018)
PARI's main goal is to contribute to sustainable agricultural growth and food security in Africa and India by supporting the scaling of proven innovations in the agri-food sector in collaboration with all relevant actors. PARI accompanies specified innovations with ex-ante impact research and identifies further innovation opportunities, including those expressed by end users of research in collaboration with the multi-stakeholder innovation platforms. Within PARI's work, AGRODEP and IFPRI have the task of assisting in the development of a methodology and concept for strategic analysis and visioning by providing economic modelling tools to help understand where the best opportunities for innovation investments in value chains are. For this purpose, IFPRI has constructed agricultural typologies of micro-regions for 8 of the 12 African countries in PARI to identify micro-regional level opportunities, bottlenecks and investment gaps based on the concept of the production possibilities frontier applied to farm activities, drawing on highly detailed household-level survey and geospatial data on agroecological conditions, accessibility and poverty. The stochastic frontier approach allows the econometric exploration of the notion that, given the fixed local agroecological and economic conditions in a micro-region and the occurrence of random shocks that affect agricultural production (weather, prices, etc.), the investment, production decisions and technological innovations a farmer makes translate into higher or lower production and income. In such a context, inefficiency is defined as the loss incurred in by operating away from the frontier given the current prices and fixed factors faced by the household. By estimating where the frontier lies, and how far each producer is from it, the stochastic frontier approach helps to identify local potential and efficiency levels to construct the typology. With this estimation approach estimates are obtained that allow for the prediction and extrapolation of agricultural income potential and efficiency measures at the regional level, which can then be grouped and classified into types to construct the typology. The typology then allows the identification of types of regions with extremely different needs, bottlenecks and opportunities, which in turn will result in a different set of investment recommendations for development in each type of region, including decisions regarding investments in agricultural innovation.
Keywords: D24; O13; Q18; R11; R12; 330; Production Efficiency Measures; Agricultural Policy; Rural Development; Economic Geography